FUNCTIONAL DEGRADATION OF FIDUCIARY CREDITOR'S PREFERENT RIGHTS AFTER THE CONSTITUTIONAL COURT'S DECISION - Restu Arif Hanavi; Tuhana; Agus Riwanto (RADJA PUBLIKA, 2026)
This article analyzes the functional degradation of fiduciary creditors' preferential rights after Constitutional Court Decision Number 18/PUU-XVII/2019. The study argues that the decision did not abolish fiduciary creditors' preferential rights, but transformed their practical realization from direct parate execution into conditional parate execution. Using normative legal research with statutory, case, and conceptual approaches, supported by documented socio-legal cases, this article examines the relationship between Article 15, Article 27, and Article 29 of the Fiduciary Security Law and the Constitutional Court's interpretation of default and voluntary surrender. The findings show that before the decision, fiduciary certificates and parate execution strengthened the economic value of preferential rights, but also enabled unilateral repossession practices. After the decision, debtor protection increased, yet disputed default or refusal to surrender the collateral creates procedural similarities with ordinary debt-collection disputes and produces economic consequences for creditors through higher transaction costs, longer recovery time, depreciation risks, and weaker recovery certainty.